Surgical Removal of Endometrioma Decreases the NF-kB1 (p50/105) and NF-kB p65 (Rel A) Expression in the Eutopic Endometrium During the Implantation Window - Celik, Onder; Celik, Ebru; Turkcuoglu, Ilgin; Yilmaz, Ercan; Ulas, Mustafa; Simsek, Yavuz; Unlu, Cihat (Sage Publications Inc, 2013)
We aimed to investigate whether the surgical removal of endometrioma alters the nuclear factor-kappa B1 (NF-kB1; p50/105) and NF-kB p65 (Rel A) expression in the eutopic endometrium of infertile women with endometrioma before and after laparoscopic removal of the ovarian endometrioma during the mid-secretory phase. Infertile women with endometrioma (n = 15) were enrolled. Infertile patients with nonendometriotic ovarian cyst (n = 10) and healthy fertile women (n = 10) were recruited as controls. Endometrial samples were obtained before and 3 months after the laparoscopic cystectomy. The NF-kB1 (p50/105) levels were analyzed by enzyme-linked immunosorbent assay (ELISA) in the endometrium of all groups before and after laparoscopic ovarian cystectomy during implantation window. Expression of NF-kB1 (p50/105) in eutopic endometrium was significantly higher in infertile women with endometrioma compared to nonendometriotic cyst and fertile controls (P < .05). Laparoscopic cystectomy resulted in a significant decrease in NF-kB1 expression in women with endometrioma. The NF-kB p65 (Rel A) immunoreactivity of eutopic endometrium decreased significantly subsequent to the surgical removal of the endometrioma. In conclusion, increased endometrial NF-kB expression may contribute to endometriosis-associated infertility.
Keywords: endometrioma; eutopic endometrium; laparoscopy; NF-kB1; NF-kB p65 (Rel A)